The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1016/s0360-3016(97)00129-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia and incorporation of halogenated pyrimidines: Radiosensitization in cultured rodent and human tumor cells

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…The effects of combining hyperthermia with radiation sensitization by halogenated pyrimidines on PLD were studied by Van Bree et al (1997). It has been suggested that radiation sensitization by HP might be attributed to the conversion of low LET lesions into high LET lesions through an increase in the clustering or severity of radiation-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of combining hyperthermia with radiation sensitization by halogenated pyrimidines on PLD were studied by Van Bree et al (1997). It has been suggested that radiation sensitization by HP might be attributed to the conversion of low LET lesions into high LET lesions through an increase in the clustering or severity of radiation-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of former studies conducted by our laboratory, radiation sensitisation by a variety of agents in different types of mammalian cells has been investigated and cell survival curves have been analysed using the LQ model (5)(6)(7)(8)(9)(10)(11). Radiation enhancement could thus be assessed in separate α-and β-values and in the α/β ratio.…”
Section: Cell Survival and Radiosensitisation: Modulation Of The Linementioning
confidence: 99%
“…Incorporation of halogenated pyrimidines (HPs), chloro-, bromo-and iodo-deoxyuridine (CldUrd, BrdUrd, IdUrd) into DNA is known to sensitise cells to ionizing radiation (6,8,11,(86)(87)(88)(89)(90)(91)(92)(93). The induced radiosensitisation increases with the degree of thymidine replacement.…”
Section: Halogenated Pyrimidinesmentioning
confidence: 99%
“…Incorporation of halogenated pyrimidines (HPs), chloro-, bromo-and iodo-deoxyuridine (CldUrd, BrdUrd, IdUrd) into DNA is known to sensitise cells to ionizing radiation (Franken et al 1997ab, 1999ab;van Bree et al 1997;Iliakis et al 1999;Miller et al 1992ab). The induced radiosensitisation increases with the degree of thymidine-replacement.…”
Section: Halogenated Pyrimidinesmentioning
confidence: 99%
“…An additional advantage of the LQ model is that its parameters can be discussed in terms of specific mechanisms of cell inactivation by radiation (Barendsen, 1990(Barendsen, , 1994. Linear-quadratic analyses of hyperthermia-or chemotherapy-induced radiation sensitisation have been reported for exponentially growing and plateau phase human tumour cells in culture and for different experimental rodent cell lines (Franken et al, 1997a(Franken et al, , 1997bvan Bree et al, 1997van Bree et al, , 2000Castro Kreder et al, 2004;Bergs et al, 2006. When the additional treatment results in increases of the value of the -parameter, this indicates that this treatment radiosensitizes at clinically relevant doses.…”
mentioning
confidence: 99%